Oestrogen-dependent regulation of miRNA biogenesis: many ways to skin the cat. (20th July 2012) - Gupta, Ananya; Caffrey, Emer; Callagy, Grace; Gupta, Sanjeev
Abstract : The steroid hormone oestrogen is central to normal female physiology, reproduction and behaviour, through its effects on cellular processes including cell proliferation and cell survival. The effects of oestrogen are mediated by nuclear ERs (oestrogen receptors). ER status is important for the development, progression and treatment of breast cancer. miRNAs (microRNAs) are small non-coding RNAs that bind the 3′-UTR (untranslated region) of target mRNAs to reduce their stability and/or translation. miRNAs participate in oestrogen signalling by regulating oestrogen-responsive genes and pathways. Interestingly expression and maturation of miRNAs can also be regulated by ER signalling at multiple levels. In addition to regulating the expression of miRNAs at the transcriptional level, ER appears to be able to regulate the biogenesis of miRNAs. In the present review, we summarize recent findings on miRNA biogenesis and describe various mechanisms by which oestrogen signalling can modulate the production of miRNAs.